A comparison and review of three sets of classification criteria for systemic lupus erythematosus for distinguishing systemic lupus erythematosus from pure mucocutaneous manifestations in the lupus disease spectrum. (December 2020) - Jin, Hui; Huang, Tao; Wu, Ruifang; Zhao, Ming; Wu, Haijing; Long, Hai; Yin, Heng; Liao, Jieyue; Luo, Shuangyan; Liu, Yu; Zhang, Qing; Zhang, Peng; et al.
Although the original purpose of the systemic lupus erythematosus (SLE) classification criteria was to distinguish SLE from other mimic diseases, and to facilitate sample selection in scientific research, they have become widely used as diagnostic criteria in clinical situations. It is not known yet if regarding classification criteria as diagnostic criteria, what problems might be encountered? This is the first study comparing the three sets of classification criteria for SLE, the 1997 American College of Rheumatology (ACR'97), 2012 Systemic Lupus International Collaborating Clinics (SLICC'12) and 2019 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR'19), for their ability to distinguish patients with SLE from patients with pure mucocutaneous manifestations (isolated cutaneous lupus erythematosus without internal disease, i-CLE) in the lupus disease spectrum. 1, 865 patients with SLE and 232 patients with i-CLE were recruited from a multicenter study. We found that, due to low specificity, none of the three criteria are adept at distinguishing patients with SLE from patients with i-CLE. SLICC'12 performed best among the original three criteria, but if a positive ANA was removed as an entry criterion, EULAR/ACR'19 would performed better. A review of previous studies that compared the three sets of criteria was presented in this work.